Transformasi Pembelajaran Fisika dengan Virtual Lab: Dampaknya Terhadap Minat Belajar Siswa SMA: Penelitian - Faruq Haroky; Nadia Luanda Septania; Rifa Lihayati; Vicky Hidantikarnillah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study analyzes the effect of using a virtual lab on the interest and learning outcomes of high school students in physics on the material of forms and energy changes. The research method used was a quasi-experimental design with a pretest-posttest control group design. The research sample consisted of 60 students of grade X of SMAN 30 Tangerang Regency who were divided into two groups, namely the experimental class and the control class. The results showed that the average post-test of the experimental class reached 90.00, higher than the control class which was only 59.69. The independent t-test produced a t-count value = 8.308 greater than the t-table = 1.671 at a significance level of 0.05, which means there is a significant difference in learning interest between the two groups. These findings indicate that PhET simulations not only improve the understanding of abstract physics concepts through interactive visualization, but also can foster students' learning interest. Thus, the use of PhET-based virtual labs can be an effective strategy in physics learning to overcome the limitations of real laboratories while supporting the achievement of 21st-century learning objectives.